Keunggulan Membunuh Keunggulan: Kotak Hitam Perguruan Tinggi Mengelola Ketegangan antara Kualitas, Reputasi dan Keunggulan Versus Learning Outcome - Tamam, Mohammad Badru (Ta'dibia: Jurnal Ilmiah Pendidikan Agama Islam, 2019)
The task of higher education is to analyze public policy in determining whether the policy advances or slows the realization of the basic goals of humans and humanity, what and how existing policies should be changed. This article aims to describe how college black boxes manage the tension between quality, reputation and excellence. This research is a qualitative participatory study, the research design is a reflexive process that operates through each stage of the activity of collecting and analyzing data. Data is collected using literature study techniques and documentation studies, then analyzed by systematic cross-case comparisons from a number of case studies. From the discussion it can be concluded as follows: 1) Higher education in order to be able to survive today and in the future needs to involve industry professionals in the education process. 2) The evolution of higher education governance systems at the macro level, both at the local, national and international levels, has different ways and institutional patterns towards the same type and model that crystallized historically in the search for quality, reputation and excellence. 3) Learning outcome contributes to the level and dimension of education which represents a way to communicate external reference points at regional, national and international levels.